EXPLORATION OF FACTORS CAUSING DIFFICULTIES IN LEARNING MATHEMATICS IN ELEMENTARY SCHOOL STUDENTS - Saifatut Diniyah; Evvy Lusiana; Aziz Nuri Satriyawan (LPPM STAI Muhammadiyah Probolinggo, 2026)
In general, elementary school students consider mathematics as a subject that requires in-depth understanding due to its abstract nature. This study aims to identify the factors causing difficulties in learning mathematics in fourth-grade students of MI Al Ma'arif Sidolaju. This study is a qualitative study with a case study approach, the methods used are observation, interviews, and documentation. The research subjects included the principal, teachers, and 8 fourth-grade students. Data analysis used in this study were data reduction, data presentation, and drawing and verifying conclusions. The results of the data analysis indicate that the learning difficulties of MI Al Ma'arif Sidolaju students are difficulty understanding basic concepts, difficulty remembering formulas, difficulty understanding and solving problems. Factors causing difficulties in learning mathematics are internal factors, namely lack of basic skills, learning motivation, and physical health, external factors, namely the use of media or learning aids, and family situations. Various efforts made by teachers in overcoming learning difficulties are by providing motivation, providing learning assistance, establishing communication with parents, and designing more innovative learning. Thus, through this study, it can provide a deep understanding in developing effective learning.